(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
The nature of terrorism has changed significantly over the last decade. In recent years, the phenomenon of so-called lone wolf terrorism has increased with more and more attacks perpetrated by single actors. The shifting nature of terrorism has prompted a debate over how to accurately describe individuals that act independently of a terrorist organization’s chain of command. The lone wolf concept needs to be re-evaluated and adapted to changed circumstances. The purpose of this paper will be focused on one of the most unpredictable forms of terrorism acts - those committed by a single individual, a so-called ”lone wolf terrorist”. Politically, the concept lone wolf is used to reassure the public and communicate that the danger is no longer immanent. Academically as well as practically, the concept entails more than this reassurance. The most difficult part in detecting a lone wolf is that their attacks occur in the context of multiple ideological frameworks and are not confined to a single group or system of belief. Currently, there are more questions than answers on the content and validity of the lone wolf concept, but we should be alert and aware that the external conditions have changed, and old responses may not be appropriate anymore to present-day lone actor terrorism.